Economic Dynamics of Fisheries Penjajap Village Pemangkat: An Analysis of the Role of Fish Auction Sites in Improving the Welfare of Local Fishermen - Hartono, Rudi (Institut Riset dan Publikasi Asas Nusantara., 2024)
The fish auction in Penjajap Village, Pemangkat Subdistrict, Sambas Regency, West Kalimantan, plays an important role as an economic center for local fishermen. However, this auction activity faces challenges in the form of fluctuating fish prices, the dominance of large capital, and dependence on markets outside the region, which can affect the welfare of fishermen. This research was conducted to address the knowledge gap regarding the role of fish auctions in supporting fishermen's economic welfare and to identify the constraints faced in the auction system. Using a case study-based qualitative approach, data was collected through in-depth interviews, direct observation, and document analysis from fishermen, traders, as well as related parties such as the Fisheries Agency and fisheries schools. The results show that fish auctions contribute significantly to increasing fishers' income through a more competitive market mechanism, although the success still depends on the fishing season and market conditions. The dominance of well-capitalized actors in the auction system creates economic disparities among fishers, while fluctuations in fish prices affect the stability of their income. In addition, limited infrastructure and market access are major challenges in the distribution of catches to other regions. This research provides important implications for fisheries policy development that focuses on fishermen's economic sustainability, strengthening the auction system, and improving equity in market access and capital.